Pengembangan Media pembelajaran Berbasis Website Pada Pembelajaran Matematika SD Kelas 1 - Tri Agus Setiawan; Rasiban; Rizki Ananda Pratama (Jurnal Nasional Teknologi Komputer, 2022)
Web-based learning media utilizes technology. This research aims to assess the feasibility of a web-based learning media for 1st grade elementary school mathematics lessons. The objective is to develop a website as a learning platform for 1st-grade elementary school students in mathematics. The type of research used is research and development, involving three stages: preliminary study, product development, and testing. In this digital era, the use of information technology in education is increasingly crucial, and developing a website as a learning tool can be an effective solution to enhance the quality of mathematics education at the elementary school level. The website is designed to provide interactive mathematics learning content aligned with the educational curriculum. The development process includes analyzing the learning needs of 1st-grade students in mathematics, designing website content and interface, developing the website according to predefined specifications, implementing the website in classroom learning, and evaluating its effectiveness as a learning tool. The study involves 1st-grade elementary school students as trial subjects to assess the impact of the website on their interest and understanding of mathematics. Data collected are analyzed quantitatively and qualitatively to measure the success rate and usability of the website in the context of mathematics learning.